1987
DOI: 10.1177/109019818701400302
|View full text |Cite
|
Sign up to set email alerts
|

A School Health Education Program for Children with Asthma Aged 8-11 Years

Abstract: It was hypothesized that a health education program for children with asthma aged 8-11 years that was delivered in elementary schools, would increase children's asthma management skills, self-efficacy and influence on parents' management decisions; reduce school absences and improve school performance. The study population consisted of 239 low-income, predominantly Hispanic and black children from 12 elementary schools (six experimental and six control) in New York City. Parents did not attend educational sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
1
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(130 citation statements)
references
References 18 publications
3
124
1
2
Order By: Relevance
“…72 Open Airways for Schools has been shown to increase school performance and self-management behaviors and to decrease the number of asthma episodes. 73 CONCLUSIONS Analysis of the current burden of childhood asthma yields a mixture of positive and negative findings. Prevalence trends have plateaued and asthma-related death rates have decreased.…”
Section: Minority Children Have a Critical Need For Improved Intervenmentioning
confidence: 99%
“…72 Open Airways for Schools has been shown to increase school performance and self-management behaviors and to decrease the number of asthma episodes. 73 CONCLUSIONS Analysis of the current burden of childhood asthma yields a mixture of positive and negative findings. Prevalence trends have plateaued and asthma-related death rates have decreased.…”
Section: Minority Children Have a Critical Need For Improved Intervenmentioning
confidence: 99%
“…Evans et al 17 provided comprehensive asthma selfmanagement education for children in low-income, minority, elementary schools; subsequently, children in the treatment schools experienced significantly fewer 20 (2001) 272 Peer education on asthma management Improved quality of life and reduction in absenteeism Guo et al 21 (2005) 273 School-based asthma clinic Reductions in hospital and emergency department visits and care costs Tinkelman and Schwartz 18 (2004) 41 Asthma self-management education Reductions in missed school days, unscheduled doctor visits, and symptoms Halterman et al 22 (2004) 180 Asthma medications provided at school Reductions in missed school days and symptoms Clark et al 19 (2004) 835 Comprehensive management education Reductions in symptoms in persistent group; better grades; fewer missed school days asthma symptoms, had fewer emergency department visits, and had better grades in school, compared with control subjects. In a smaller study, Tinkelman and Schwartz 18 also found positive results for school-based asthma education, that is, the children had fewer asthma symptoms, less absenteeism, and fewer unscheduled doctor visits.…”
Section: School-based Interventionsmentioning
confidence: 99%
“…17 First, asthma is still at an unacceptable level of prevalence. Second, the plateauing has not occurred in the low-income and minority communities that experience the greatest burden of disease.…”
Section: Challenges To Moving Research and Practice Forwardmentioning
confidence: 99%
“…Two studies were published in the 1970s (Alexander, 1972, 363 Davis 382,383 ), eight in the 1980s (Alexander, 1988, 402 Backman, 385 Evans, 403 Gold, 418 Gustafsson, 419,420 McNabb, [412][413][414][415] Mitchell, 376 Westphal 410 ), 16 in the 1990s (Colland, 378 Collins, 407 Dahl, 381 Fisher, 408,409 Garrett, 404 Greineder, ). The breakdown of studies by decade of publication according to the main type of intervention evaluated is shown in Figure 4.…”
Section: Publication Datesmentioning
confidence: 99%